The Health Reframing of Climate Change and the Poverty of Narrow Bioethics. Issue 4 (December 2020) - Ferguson, Kyle
We must resist thoroughly reframing climate change as a health issue. For human health–centric ethical frameworks omit dimensions of value that we must duly consider. We need a new, an environmental, research ethic, one that we can use to more completely and impartially evaluate proposed research on mitigation and adaptation strategies.